Sudamérica Futuro: China global, transición energética y posdesarrollo - Fornillo, Bruno (CLACSO, 2016)
South America Future. Global China, energy transition and post-development addresses the situation that is emerging in South America as a result of global environmental change, the decline of the fossil energy pattern and the huge Asian reemergence. At the beginning, it presents the scenario open to the "confrontation of the Pacific", which opposes the interests of the US power to the rising China, originating a global inter-imperial tension that has a decisive impact on the Southern Hemisphere. In this framework, he discusses the place reserved for our subcontinent as an exporter of nature, energy and work, in order to think about how to consider our natural wealth, the energy transition, the ways of articulation between science, industry and politics, envisioning a new path to post-development. At the same time, it historicizes the rich tradition of geopolitical thought in the region, which has known how to have a decisive influence on the orientation of our states, and which today feeds on new aspects. Sudamérica Futuro brings up current problems whose consequences are open to a wide horizon of time, in which the subsumption of nature is mixed with an irreducible tension between capital and living labor.